Manfaat dan tantangan implementasi konsultasi kesehatan mental daring di Indonesia: Survei pada praktisi - Retha Arjadi; Sri Juwita Kusumawardhani; Natasha Purnomo; Claudi L. Bockting (Konsorsium Psikologi Ilmiah Nusantara, 2023)
The use of online mental health consultation is increasing in Indonesia, especially since the Covid-19 pandemic. This study investigates the benefits and challenges in implementing online mental health consultation in Indonesia, from the practitioners’ perspectives. A total of 210 mental health practitioners participated in this online survey study. The most frequently reported benefits of delivering online consultation were location flexibility and time flexibility. Meanwhile, the most frequently reported challenges were limited non-verbal communication and difficulty in delivering certain psychological assessments to clients. Moreover, participants express the needs for supports from relevant professional organizations and the government, especially in terms of clear regulations for the use of digital technology in mental health consultation. This research showed important insights from mental health practitioners, and practical recommendations as well as suggestions for further research were discussed.